PENGUATAN PEMBELAJARAN IPS TERPADU SEBAGAI ALTERNATIF PENANGGULANGAN DISORIENTASI PERILAKU SOSIAL PESERTA DIDIK DI ERA GLOBALISASI - Krisnoviani; Ibrahim; Hasni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the Strengthening of Integrated Social Studies Learning as an Alternative to Addressing Disorientation in Students' Social Behavior in the Era of Globalization through a literature review method. This study uses a qualitative approach with a literature review method that examines several relevant scientific articles. The results of the study indicate that the development of globalization has influenced changes in students' social behavior, such as decreased social awareness, weakened tolerance, increased individualistic behavior, and low social responsibility. Integrated social studies learning plays a crucial role in shaping and strengthening students' social values ​​through the integration of various social science disciplines such as geography, history, economics, and sociology into contextual learning. Through an active, participatory learning approach based on social problem-solving, students can develop social awareness, tolerance, critical thinking skills, and the ability to collaborate. Therefore, strengthening integrated social studies learning can be an effective alternative to addressing disorientation in students' social behavior in the era of globalization.